Strategi Penyesuaian Diri Mahasiswa Papua Fakultas Ilmu Budaya Universitas Halu Oleo Di Kota Kendari - Agustina, Agustina; Hasniah, Hasniah (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims to understand how Papuan students at the Faculty of Cultural Sciences, Halu Oleo University, adapt to their environment. It seeks to explore: (1) What problems are faced by Papuan students at the Faculty of Cultural Sciences, Halu Oleo University, in Kendari City; and (2) How these students overcome the challenges they encounter. The study employs the theory of Functionalism by Talcott Parsons (AGIL theory). The research method used is qualitative with purposive sampling. Data were analyzed using the following techniques: descriptive analysis based on observations, interviews, and documentation. The qualitative descriptive analysis describes the research findings based on field data, followed by interpretation and conclusion. The results show that Papuan students adapt to the challenges they face by adjusting their language style to the new environment—learning the daily language used by students from other ethnic groups to facilitate communication. They also adapt socially by becoming accustomed to interacting with peers, cooking for themselves, and adjusting to new food preferences that differ significantly from their traditional cuisine. Additionally, they stay indoors in the late afternoon to avoid symptoms such as dizziness, skin redness, peeling, and chills. They also comply with dormitory rules to avoid hindrances in the adaptation process.